Absence of telomerase activity and telomerase catalytic subunit mRNA in melanocyte cultures - Dhaene, K (Nature Publishing Group, 2000)
The classic model of activation of telomerase, for which activity has been found in most cancers including cutaneous malignant melanoma (CMM), dictates that enzyme activity is generated by pathological reactivation of telomerase in telomerase-negative somatic cells. However, recent data demonstrated physiological up-regulation in some normal cell types when established as proliferating cultures, indicating that, in some cancer types, telomerase is expressed by the process of up-regulation in telomerase-competent precursor cells. In this study, cultures of epidermal melanocytes, progenitor cells of CMM, were established and harvested in the logarithmic phase of growth. Telomerase activity was looked for using a non-isotopic variant of the telomeric repeat amplification protocol, and transcript expression of the hTERT gene, the rate-limiting catalytic telomerase subunit, was investigated by the reverse transcription polymerase chain reaction. Neither telomerase activity nor hTERT mRNA could be detected in proliferating melanocyte cultures. Our in vitro data argue against the model of telomerase as a common biomarker of cell proliferation. The results further suggest that telomerase is tightly controlled in normal melanocytes, and that telomerase is reactivated rather than up-regulated in melanocytic precursors during melanoma initiation or progression. © 2000 Cancer Research Campaign